PENGEMBANGAN LEMBAR KERJA SISWA (LKS) MATEMATIKA BERBASIS PROBLEM SOLVING PADA SISWA KELAS III SD NEGERI 1 WIDODO - P, Windy Herdiyanti; Asep Sukenda Egok; Elya Rosalina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop valid, practical, and effective Problem Solving-based Mathematics Student Worksheets (LKS) for grade III students of SD Negeri 1 Widodo. The LKS previously used at SD Negeri 1 Widodo were still monotonous (black and white text and images) and the material presented was incomplete, resulting in a lack of student enthusiasm and the Minimum Completion Criteria (KKM) of 65 not being achieved in mathematics learning. This study used the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The LKS design was created using the Canva application. The results of the study showed that the LKS developed had a